1991
DOI: 10.1016/s0022-5347(17)38165-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Transrectal Ultrasonography in Modified Stamey Procedure for Stress Urinary Incontinence

Abstract: From June 1989 to August 1990, 21 women with genuine stress urinary incontinence were treated with the Gittes procedure combined with transrectal ultrasonography. The urethrovesical junction was well pinpointed on an ultrasonographic image. The strength of suspension providing the optimal posterior urethrovesical angle was changed by each patient. Posterior urethrovesical angles averaged 89.3 +/- 9.5 degrees at operation and 93.6 +/- 9.5 degrees (mean +/- standard deviation) on a postoperative lateral cystoure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…All the authors [32][33][34][35] who perform introital ultrasonography used the PUVA as a criterion. It was also used by the authors who performed perineal ultrasonography [23] and transrectal ultrasonography [51,53], but not in transvaginal ultrasonography. Some authors state that the PUVA is not discriminate for SUI [30,38,40,52].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the authors [32][33][34][35] who perform introital ultrasonography used the PUVA as a criterion. It was also used by the authors who performed perineal ultrasonography [23] and transrectal ultrasonography [51,53], but not in transvaginal ultrasonography. Some authors state that the PUVA is not discriminate for SUI [30,38,40,52].…”
Section: Resultsmentioning
confidence: 99%
“…Yamada et al [53] performed transrectal ultrasonography before the Stamey operation and during the operation on the cases with SUI. They set the PUVA at 80-100 ~ and fastened the suture materials.…”
Section: Transrectal Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of these procedures can not achieve this goal mainly due to inappropriate methods or technical failures. Ultrasonography has been used for postoperative evaluation of patients to document the reasons of failed operations (4–7). These evaluations suggested that patients with successful operations had beneficial stabilization of the bladder necks by surgical repair, while those with persistent or recurrent incontinence were associated with reacquisition of the bladder neck hypermobility (4–9).…”
mentioning
confidence: 99%
“…Ultrasonography has been used for postoperative evaluation of patients to document the reasons of failed operations (4–7). These evaluations suggested that patients with successful operations had beneficial stabilization of the bladder necks by surgical repair, while those with persistent or recurrent incontinence were associated with reacquisition of the bladder neck hypermobility (4–9). Although, several different measurement methods have been proposed to objectively document the position or the mobility of the bladder neck, the effectiveness of these methods was controversial (4–13).…”
mentioning
confidence: 99%